The Effect Of Liquid Organic Fertilizer And Solid Organic Fertilizer On The Growth And Production Of Eggplant (Solanum melongena L.) - Ernitha Panjaitan; Pahala L.L.Sianturi; Lamria Sidauruk; Evita Yusniati Manurung (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This study aims to determine the effect of liquid organic fertilizer and solid organic fertilizer on the growth and production of eggplant (Solanum melongena L). This study used a Factorial Randomized Group Design (RAK). The first factor is liquid organic fertilizer (POC) consisting of 4 treatment levels, namely: A0 = 0 ml/l (control), A1 = 2.5 ml/l, A2 = 5 ml/l and A3 = 7.5 ml/l. The second factor is solid organic fertilizer (POP) consisting of 3 treatment levels, namely: P1 = 600 g/plot (3 tons/ha), P2 = 1000 g/plot (5 tons/ha) and P3 = 1400 g/plot (7 tons/ha). The results showed that liquid organic fertilizer had a significant effect on plant height, number of leaves, number of fruits per plant, production weight per plant and production weight per plot but had no significant effect on the number of flowers, fruit length and weight per fruit. Solid organic fertilizer had a significant effect on plant height, number of leaves, number of fruits per plant, production weight per plant and production weight per plot but had no significant effect on the number of flowers, fruit length and weight per fruit. The interaction of liquid and solid organic fertilizers had no significant effect on plant height, number of leaves, number of flowers, number of fruits per plant, production weight per plant, production weight per plot, fruit length and weight per fruit.